Hennes & Mauritz (H&M). A : standing up for human rights in China - Derr, Timothy; Raley, Madison; Shea, Caitlin; Siegman, Jackson; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2021)
Following reports of forced labor in its supply chain, fast fashion merchandiser H&M stopped sourcing cotton from China's Xinjiang region, the site of alleged genocide. After Western sanctions sparked nationalist outrage, China retaliated by boycotting H&M. Will H&M continue defending human rights or choose to preserve the growing Chinese market?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- Case studies; Business logistics -- Case studies